A 2-year study on milk quality from three pasture-based dairy systems of contrasting production intensities in Wales. (30th September 2014) - STERGIADIS, S.; LEIFERT, C.; SEAL, C. J.; EYRE, M. D.; LARSEN, M. K.; SLOTS, T.; NIELSEN, J. H.; BUTLER, G.
SUMMARY: There is an increasing interest in pasture-based dairy systems in Europe, mainly because of increasing production costs for intensive dairying. Milk is a matrix of compounds that influence nutritional and manufacturing properties, many dependent on husbandry linked to pasture-based systems (increase in pasture intake, forage : concentrate ratio, clover inclusion in swards/silages and use of alternative dairy breeds). The present study investigated the impact of three grazing-based dairy systems with contrasting feeding intensity or reliance on pasture intakes (conventional high-intensity, low pasture intake [CH], organic medium-intensity, medium pasture intake [OM], conventional low-intensity, high pasture intake [CL]) on milk fatty acid (FA) profiles, protein composition and α -tocopherol and antioxidants concentrations. The proportion of animals of alternative breeds (e.g. Jersey) and crossbred cows in the herd increased with decreasing production intensity (CH < OM < CL). Milk constituents known to be beneficial for human health, such as vaccenic acid, rumenic acid, monounsaturated FA, polyunsaturated FA, antioxidants and caseins, were elevated with decreasing production intensity (CH < OM < CL), while less desirable saturated FA were lower, although not all differences between OM and CL were significant. Omega-3 FA were maximized under OM practices, primarily as a result of higher clover intake. Increases in pasture intake may explain the higher concentrations of desirable FA while increased use of crossbreed cows is likely to be responsible for higher total protein and casein content of milk; a combination of these two factors may explain increased antioxidant levels. The higher concentrations of vaccenic acid, rumenic acid, omega-3 FA, lutein, zeaxanthin, protein and casein in OM and CL milk were found over most sampling months and in both years, reinforcing the higher nutritional quality and manufacturing properties associated with milk from these systems. A switch to pasture-based dairy products would increase the intake of milk's beneficial compounds and reduce consumption of less desirable saturated FA.